Early screening diagnostic test in adolescents with a family history of thalassemia - Natiqotul Fatkhiyah; Apoina Kartini; Sri Achadi Nugraheni; Ani Margawati; Fatchurrozak Himawan (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Thalassemia is a major public health concern in Indonesia, particularly in families with a known history of the ailment. This study aimed to assess the validity, reliability, sensitivity, and specificity of a thalassemia screening instrument that included a questionnaire and a scoring model. Methods: A cross-sectional study was conducted in Tegal, Central Java (November 2024–April 2025), involving 64 adolescents aged 10–24 years from extended families with a history of thalassemia, selected through purposive sampling. Inclusion criteria included willingness to participate, ability to communicate, and signed informed consent, while exclusion criteria included incomplete participation, other blood disorders, medical complications, or withdrawal. Screening consisted of a structured questionnaire and physical examination (score 0–8), followed by CBC and HbA2 testing. Statistical analyses included the Kolmogorov–Smirnov test, chi-square tests, Pearson or Spearman correlations, and diagnostic accuracy measures (sensitivity, specificity, PPV, NPV) using a 2×2 table. Results: The screening instrument showed a sensitivity of 76.5%, a specificity of 85.6%, and an AUC of 0.76. It demonstrated acceptable internal consistency and significant construct validity, indicating moderate diagnostic accuracy for identifying thalassemia trait. Conclusion: The screening tool established in this study was appropriate for teenagers with a family history of thalassemia and had modest diagnostic performance. Integration into existing public health systems is both achievable and recommended.